ChemInform Abstract: Exploring 6‐(Substituted sulfonyl)imidazopyridines as a Potential Scaffold for the Design of 5‐HT6 Ligands. Issue 30 (4th July 2013) - Heloire, Valeria Moas; Furman, Christophe; Melnyk, Patricia; Carato, Pascal
Abstract Novel imidazopyridine derivatives such as (X) are designed, synthesized, and evaluated for their ability to interact with 5‐HT6 receptors.